The role of early detection and treatment in malaria elimination - Nosten, F; Landier, J; Parker, D; Thu, A; Carrara, V; Lwin, K; Bonnington, C; Pukrittayakamee, S; Delmas, G (BioMed Central, 2016)
Falciparum malaria persists in hard-to-reach areas or demographic groups that are missed by conventional healthcare systems but could be reached by trained community members in a malaria post (MP). The main focus of a MP is to provide uninterrupted and rapid access to rapid diagnostic tests (RDTs) and artemisinin-based combination therapy (ACT) too all inhabitants of a village. RDTs allow trained community members to perform malaria diagnosis accurately and prescribe appropriate treatment, reducing as much as possible any delay between the onset of fever and treatment. Early treatment with ACT and with a low-dose of primaquine prevents further transmission from human to mosquito. A functioning MP represents an essential component of any malaria elimination strategy. Implementing large-scale, high-coverage, community-based early diagnosis and treatment (EDT) through MPs requires few technological innovations but relies on a very well structured organization able to train, supervise and supply MPs, to monitor activity and to perform strict malaria surveillance.